We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
46
2
avatar+60 

ggghhhhhhhhhhhhhh

 Nov 18, 2019
edited by shgg111  Nov 18, 2019
 #1
avatar+105370 
+2

Using the equation  of the line

2x + 3y  = 3

3y = 3  - 2x

y =  (3 - 2x)  /3

 

Let  the center of the circle be  ( x, (3 -2x) / 3  )

 

And  the distance from this center  to both of the given  points is  equal ....so...

 

(x -8)^2  + [ (3 -2x)/3  + 5]^2   =   ( x + 1)^2 + [ (3 -2x)/3 -4 ] ^2    simplify

 

x^2 - 16x + 64  +  [ (18 -2x)/ 3 ]^2  =  x^2 + 2x + 1 +  [ (-9 - 2x) / 3 ] ^2

 

x^2 - 16x+ 64 + [ 324 - 72x + 4x^2/] /9  = x^2 + 2x + 1  + [ 81 + 36x + 4x^2 ] / 9

 

-16x + 64  + [ 324 - 72x + 4x^2 ] / 9  =  2x + 1 + [81  +36x+ 4x^2]/9      multiply through by 9

 

-144x + 576 + 324 - 72x + 4x^2 =  18x + 9 + 81 + 36x + 4x^2

 

-216x + 900 = 90 + 54x

 

810  = 270 x     divide both sides by 270

 

3  = x

 

And using the equation of the line     y = [ 3 - 2(3)] / 3  = -1

 

So...the center of the circle is  (3 , -1)

 

And using either point and this center, we can find r^2  as

 

(8 - 3)^2 + ( -5 + 1)^2  = r^2

 

5^2 + (-4)^2 = r^2

 

41  = r^2

 

So...the eqaution is  ( x - 3)^2 + ( y + 1)^2  =  41

 

Here's the graph : https://www.desmos.com/calculator/20kbuxcqtc

 

 

cool cool cool

 Nov 18, 2019
 #2
avatar+60 
+2

thank you 

shgg111  Nov 18, 2019

35 Online Users

avatar
avatar
avatar